Rapid Batch Method for the Preparation of Fluorescein Isothiocyanate-Conjugated Antibody - Calcagno, John V. (1973)
A rapid, reproducible, and relatively simple method for the preparation of large quantities of fluorescein isothiocyanate-conjugated antibody is presented. Tagged globulins with fluorochrome-protein ratios of 1 and 2 were eluted from diethylaminoethyl-cellulose in batch form by using sodium phosphate-buffered 0.1 M and 0.2 M saline, respectively. The intensity and specificity of the fluorescence due to this antibody was quite high, as determined by the ability of untagged antibody to block the immunological reactivity of the fluorescent antibody and by the lack of fluorescence of antigenically unrelated material when treated under identical conditions.